Fast boat to China : high-tech outsourcing and the consequences of free trade - lessons from Shanghai - Ross, Andrew (Vintage Books New YorkUS, 2007)
Shows how the Chinese workforce has inherited many of the same worries as American workers and face the consequences, such as job instability, long hours and awareness of their own expendability. Report os the daily reality of corporate free trade and explores the growing competition between China and India.